Spillover Effects of Ingredient Branded Strategies on Brand Choice: A Field Study - Vanitha, Swaminathan (Institutional Knowledge at Singapore Management University, 2012)
Ingredient branding, or the use of two or more brand names on a single product, is widely seen as providing significant benefits in terms of increased product differentiation and greater market share. The association between two brand names can both enhance and dilute the brand equity of the host brand name and the ingredient brand name. This research examines the behavioral spillover effects associated with cobranded strategies across segments of consumers that vary in their prior brand commitment or loyalty. Different from previous research, this paper uses A.C. Nielsen scanner panel data to investigate the behavioral spillover effects of ingredient branded products on choice of the host and ingredient brands in a field setting. The results suggest that there is a significant behavioral spillover impact of trial of the cobranded product on the purchase probability of both the host and ingredient brands. This effect is greater among prior non-loyal users and prior non-users of the host and ingredient brands and when there is a higher degree of perceived fit between the host and ingredient brands.